SIMULATION STUDY ON AFFECT FACTORS OF WORKOVER STRING BUCKLING IN HORIZONTAL WELL - LIN Wei; DONG ZongZheng; ZHANG LiMin; ZHANG JianZhong; WANG HongJun (Jixie qiangdu)
Understanding the WOB and the law of tubular buckling is significant to handle workover operation efficiently and safely. Based on the simulation theory and the characteristics of workover string dynamics,a finite element model is established for the workover string. Then,the tubular in the wellbore is simulated by the model,and the simulation result is highly coincide with the experiment result. The strings in horizontal well is built,and the critical buckling load is analyzed in different friction coefficient and different annular clearance. The results show that: the sinusoidal buckling load and helical buckling load will increase with the friction coefficient,and the helical buckling load increase more rapidly; while with the increase of annular clearance,the buckling load will decrease. When the annular is larger than 35 mm,the helical buckling load is even smaller than sinusoidal buckling load.